Effects of Oral Exposure to Mn-Doped ZnS Quantum Dots on Intestinal Tract and Gut Microbiota in Mice - Yang, Yanjie; Xia, Ruixue; Zhang, Xiaomei; Wang, Xu; Zhou, Yuchen; Wang, Honggang; Feng, Yu; Lv, Shuangyu; Ji, Shaoping (Frontiers in Physiology, 2021)
Mn-doped ZnS quantum dots (QDs) with excellent optical properties have been explored in a wide range of fields. Their potential adverse effects on biological systems and human health should be evaluated before biological application. In the present study, we investigated the effect of Mn-doped ZnS QDs on the intestinal tract and gut microbiota structures at 2 h and 14 days (d) after 14 d repeated oral exposure in mice. Flame atomic absorption spectrophotometry (FAAS), histopathological examination, and transmission electron microscopy (TEM) were used to assess the absorption and toxicity of Mn-doped ZnS QDs on the intestinal tract. The 16S rRNA gene sequencing was used to evaluate the gut microbial communities. Mn-doped ZnS QDs did not accumulate in the duodenum, jejunum, ileum, or colon. The Zn content of feces was not significantly higher than in the control group. No major histological changes were found in these tissues. The intestinal microvilli remained regular, but swelling of mitochondria and endoplasmic reticulum was detected by TEM at 14 d after the last gavage. A total of 2,712 operational taxonomic units (OTUs) were generated. Mn-doped ZnS QDs treatment did not significantly change the α-diversity of Richness, Chao1, Shannon, and Simpson indexes. According to principal component analysis (PCA), Mn-doped ZnS QDs had no effect on the overall structure of the gut microbiota. No significant change occurred at the phylum level, while three genera were downregulated at 2 h and seven changed at 14 d after the last gavage. Our findings revealed that Mn-doped ZnS QDs had a little stimulation of the intestinal tract and gut microbiota, and oral administration may be a safe route for biological application (such as bioimaging and drug delivery).